2014
DOI: 10.1159/000365197
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Frequent Differentially Methylated Region in Sporadic Bladder Cancers

Abstract: Introduction: Aberrant methylation levels in the cytosine-phosphate-guanine island (CpGi) region from exon 1 to intron 1 of the zygote arrest 1 (ZAR1) gene have been reported in several types of human cancers, including melanoma, brain tumor, and hepatocellular carcinoma. In the present study, methylation levels at the CpGi of ZAR1 exon 1/intron 1 in bladder cancer specimens were analyzed using mass spectrometry. Materials and Methods: Genomic DNA was extracted from 20 sporadic bladder cancers, and the methyla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…DNA methylation is a significant epigenetic mechanism of gene regulation that can interpret the tumor genetic heterogeneity. Recent studies have demonstrated that hypomethylation of the CpG sites of ZAR1 gene was implicated in a high proportion of muscle-invasive bladder cancers [40]. …”
Section: Basis Of Tumor Heterogeneity: Genetic Heterogeneitymentioning
confidence: 99%
“…DNA methylation is a significant epigenetic mechanism of gene regulation that can interpret the tumor genetic heterogeneity. Recent studies have demonstrated that hypomethylation of the CpG sites of ZAR1 gene was implicated in a high proportion of muscle-invasive bladder cancers [40]. …”
Section: Basis Of Tumor Heterogeneity: Genetic Heterogeneitymentioning
confidence: 99%
“…In hypermethylated neuroblastoma, however, expression of ZAR1 was detected and indicated that ZAR1 knockdown promotes differentiation in neuroblastoma cells [13]. Intragenic ZAR1 methylation decreased in high-grade vs. low-grade tumours of the bladder [14]. In hepatitis C virus, positive liver cancer ZAR1 was reported to be methylated in exon 1 [15].…”
Section: Introductionmentioning
confidence: 99%
“…It was proposed that methylation-related aberrant ZAR1 expression was unlikely to be related to glioma tumorigenesis [16]. ZAR1 intragenic methylation (first exon to intron 1) in sporadic bladder cancer was decreased in high-grade vs. low-grade tumours [18]. In hepatitits C virus, positive hepatocellular carcinoma ZAR1 hypermethylation of exon 1 was found [19].…”
Section: Introductionmentioning
confidence: 99%